Utilizing TikTok Vlogs to Effectively Boost Young Learners' Speaking Proficiency - Muzammil, Lasim; Liskinasih, Ayu; Diftu, Syafadillah Wanodya Ayu (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
Mastering speaking skills poses a challenge for young learners, prompting the search for innovative solutions such as using educational tools. This study explores the impact of TikTok vlogs on the speaking skills of young learners, considering its potential as an educational tool. This study was conducted at one elementary school in Indonesia where the proficiency in speaking skills remained low. Participants of the present study were taken from 54 fourth-grade elementary students and the research utilized pre-test and post-test data analyzed through SPSS 21.00 using an Independent Sample t-test and N-Gain Test. The post-test data showed a significant result since the significance value of the post-test was 0.000 less than the significance level, 0.005, and this made the null hypothesis rejected. The N-gain score further confirmed its effectiveness, with a value of 58.76, compared to the control class's 18.42. These results highlight TikTok Vlog's positive impact, showcasing its potential in modern language education and advocating for its integration into teaching practices. Such compelling outcomes underscore the promising implications of integrating TikTok vlogs in language education, signaling a need for its broader implementation to bolster young learners' speaking skills in educational settings.